Aortoiliac occlusive disease, a silent syndrome (2019)
A 68-year-old woman with a 25.5 pack/year history of smoking consulted the emergency room for acute pelvis and oppressive lumbar pain. Symptoms began 6 months earlier with lower limbs mild pain, intermittent claudication and hypoesthesia. Two months earlier, a venous Doppler ultrasound was performed with normal findings. In the physical examination at the emergency room, no mention was made about lower extremities’ pulses. The patient did not consume medicines or report a history of diabetes or hyperlipidaemia.